Avoiding Communication Verbal and Nonverbal Dimensions of Defensiveness / Peter A. Andersen and Laura Knarr Guerrero. - Andersen, Peter A. (Distributed by ERIC Clearinghouse, 1989)
Defining defensiveness as a protective reaction resulting from fear or a threat to one's face or ego, this paper provides a perspective on both verbal and nonverbal aspects of defensiveness. First, the paper examines two trait-like communication predispositions--communication apprehension and touch avoidance--which arguably produce defensive behavior. Communication apprehensives are described as displaying three predominant interrelated behavior patterns characterized by withdrawal, reduced awareness, and tension, posited to be self-protective responses that paradoxically cause a negative spiral of fear, anxiety, and defensiveness. Similarly, while communication apprehension affects the likelihood of verbal contact, touch avoidance may affect the likelihood of nonverbal contact and increased intimacy. Next, the literature on disconfirmation (defined as behavior that causes another person to value himself less, with disconfirming communication characterized as indirect, closed, and ambiguous) is examined for its contribution to the defensiveness construct. Three different yet overlapping styles of disconfirming communication are discussed in the paper: (1) indifference; (2) imperviousness; and (3) disqualification. Finally, research on nonverbal immediacy (viewed as the inverse of defensiveness) is reviewed to derive some additional nonverbal behaviors associated with defensiveness. Seventy-one references are attached. (SR)